The microstructure investigation of thionine-graphene nanocomposite using SEM / Muhammad Aidil Ibrahim … [et al.] - Ibrahim, Muhammad Aidil; Md Jani, Nur Atikah; Tunku Kudin, Tunku Ishak; Mohd Yusof, Raihana; Ali, Ab Malik Marwan; Hassan, Oskar Hasdinor (Institute of Research Management and Innovation (IRMI), 2015)
Materials that can enhance the sensitivity and selectivity of a biosensor are greatly in demand. The nanocomposition of thionine (Th) and graphene can increase the electroconductivity of the working electrode used. Graphene is a very good electrical conductor but is also hydrophobic in nature. Composition with thionine gives it the capability to disperse well in water. Plus, thionine provides the opportunity for DNA probes to be immobilized due to the presence of the amino group in its structure. In this research, the thionine-graphene (Th-G) nanocomposite was synthesized through filtration and characterised using scanning electron microscopy (SEM) to distinguish different elements coexist in the nanocomposite and to investigate the microstructure changes of the nanocomposite to confirm the composition. Different elements were analyzed to test the presence of both thionine and graphene in the composition. Physical characterisation through SEM proved the nanocomposition was a success.